Monitoring spatial-temporal dynamics of drought over Yok Don National Park using Temperature-soil Moisture Dryness Index (TMDI) - Mai Son, Le; Nguyen Manh, Hung; Dao Duy, Toan; Tu Dinh, Duc-; Binh Tran, Thai; Le Dung, Thi Kim (Vietnam Journal of Earth Sciences, 2025)
This study investigates the spatio-temporal patterns of drought and their teleconnection with land surface properties in Yok Don National Park during the dry season using the Temperature-Soil Moisture Dryness Index (TMDI). This index is derived from the relationship between the Normalized Difference Land Heat Index and Land Surface Temperature, extracted from Landsat-8 data acquired in the mid-dry season from 2014 to 2023. Results reveal increasing drought severity starting in 2014, peaking during 2015–2016, and decreasing from 2017 to 2020. Drought conditions escalated again during 2021–2022 before moderating by 2023. These trends align with in-situ precipitation data recorded at a nearby meteorological station, highlighting varied impacts on forest types. Areas covered by deciduous broadleaf forests experienced pronounced drought effects, whereas evergreen broadleaf forests showed greater resilience. Land surface evapotranspiration rates obtained from NASA’s MOD16A2GF dataset were used to evaluate TMDI performance. During the dry seasons from 2014 to 2023, TMDI exhibited a consistent negative correlation with evapotranspiration, with coefficients ranging from -0.55 to -0.70. This demonstrates TMDI’s effectiveness in capturing land surface water availability and assessing drought conditions. The findings provide crucial insights into drought monitoring and management for Yok Don National Park and other water-scarce regions, reinforcing TMDI’s value in sustainable forest management and drought mitigation.